2008
DOI: 10.1097/hjh.0b013e3282f7cbab
|View full text |Cite
|
Sign up to set email alerts
|

The central hypotensive effect induced by α2-adrenergic receptor stimulation is dependent on endothelial nitric oxide synthase

Abstract: It is concluded that the central cardiovascular effects of alpha 2-adrenergic agonists, such as dexmedetomidine, require an intact expression of eNOS within the brain. This study raises the interesting question of whether central eNOS itself might be considered as a target for new cardiovascular drugs regardless of any activation of alpha 2-adrenergic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, all above results suggested that serum NO may play an important role in improving arterial oxygenation in ventilated lung. It is reported that Dex can induce vasodilation through activation NO synthase (NOS) [ 37 , 38 ]. In the current study, Dex significantly increased serum NO concentration, concomitant with decreased shunt fraction and increased PaO2, which indicates that Dex may have induced vasodilation in the ventilated lung by enhancing NO release.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all above results suggested that serum NO may play an important role in improving arterial oxygenation in ventilated lung. It is reported that Dex can induce vasodilation through activation NO synthase (NOS) [ 37 , 38 ]. In the current study, Dex significantly increased serum NO concentration, concomitant with decreased shunt fraction and increased PaO2, which indicates that Dex may have induced vasodilation in the ventilated lung by enhancing NO release.…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive o-3 fatty acid-deficient rats at 36 weeks, there was a significant down regulation of a 2A adrenergic receptor and b 1 adrenergic x-3 Fatty acid deficiency and hypertension DP Begg et al receptor genes compared with both sufficient groups. Importantly, the central pre-synaptic a 2A adrenergic receptor agonists are known to produce hypotension, 42 and a 2A adrenergic receptorÀ/À mice are hypertensive, 43 and unresponsive to the action of a 2 agonists. 44 Conversely, central administration of a b adrenergic receptor antagonist produces a potent hypotensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kirihara et al ( 42 ), following the administration of MMB, a reduction in blood pressure was observed until the 20 min mark, after which it stabilized during anesthesia. MMB, acting as an alpha2-adrenergic receptor agonist, is known to decrease blood pressure ( 43 ). However, Kirihara et al ( 42 ) noted a significant increase in systolic blood pressure at 10 min post-administration in the MMB group compared to the KX group.…”
Section: Discussionmentioning
confidence: 99%